2003
DOI: 10.1016/s0042-6822(02)00102-2
|View full text |Cite
|
Sign up to set email alerts
|

The Potato virus X TGBp3 protein associates with the ER network for virus cell-to-cell movement

Abstract: Potato virus X (PVX) TGBp3 is required for virus cell-to-cell movement. Cell-to-cell movement of TGBp3 was studied using biolistic bombardment of plasmids expressing GFP:TGBp3. TGBp3 moves between cells in Nicotiana benthamiana, but requires TGBp1 to move in N. tabacum leaves. In tobacco leaves GFP:TGBp3 accumulated in a pattern resembling the endoplasmic reticulum (ER). To determine if the ER network is important for GFP:TGBp3 and for PVX cell-to-cell movement, a single mutation inhibiting membrane binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 37 publications
6
72
1
5
Order By: Relevance
“…The TGB3 'signature motif', C(X 5 )G(X 6-9 )C (Morozov et al, 1991;Morozov & Solovyev, 2003), was present in all sequences. PVX TGB3 has predicted 23 aa N-terminal transmembrane and C-terminal 45 aa cytoplasmic segments (Krishnamurthy et al, 2003). SignalP identified both the PVX TGB3 N-terminal 23 aa and the AltMV TGB3 N-terminal 20 aa as SPs.…”
Section: Subcellular Localization Of Pvx and Altmv Tgb3mentioning
confidence: 99%
See 1 more Smart Citation
“…The TGB3 'signature motif', C(X 5 )G(X 6-9 )C (Morozov et al, 1991;Morozov & Solovyev, 2003), was present in all sequences. PVX TGB3 has predicted 23 aa N-terminal transmembrane and C-terminal 45 aa cytoplasmic segments (Krishnamurthy et al, 2003). SignalP identified both the PVX TGB3 N-terminal 23 aa and the AltMV TGB3 N-terminal 20 aa as SPs.…”
Section: Subcellular Localization Of Pvx and Altmv Tgb3mentioning
confidence: 99%
“…Several reports have addressed the contributions of TGB proteins to movement for WClMV (Lough et al, 1998), PVX (Ju et al, 2005;Krishnamurthy et al, 2003;Lough et al, 2000;Solovyev et al, 2000;Tamai & Meshi, 2001) and BaMV (Lin et al, 2006), and describe trans complementation of potexviral genomes with defects within the TGB through delivery of functional TGB constructs by using particle bombardment (Morozov et al, 1997), transgenic plants (Lough et al, 1998) or satellite RNA (Lin et al, 2006). Despite this body of work, 'a full understanding of the specific requirement of TGB3 and the functional interchangeability of TGB3 among different potexviruses for intercellular movement remains elusive' (Lin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to be required for the movement of White clover mosaic virus (WClMV) (Lough et al, 1998) but is not absolutely required for the movement of potato virus X (Tamai & Meshi, 2001). Recently, Krishnamurthy et al (2003) and Mitra et al (2003) have demonstrated that TGBp2 and TGBp3 are endoplasmic reticulum (ER)-targeted proteins and that ER targeting is important for virus movement.…”
Section: Introductionmentioning
confidence: 99%
“…En lo que respecta a las proteínas TGBp2 y TGBp3, son productos de menor tamaño y funcionan como proteínas integrales de membrana en ambas clases de virus [Tamai & Meshi, 2001;Cowan et al, 2002;Zamyatnin et al, 2002;Krishnamurthy et al, 2003;Gorshkova et al, 2003]. El producto TGBp2, cuyo tamaño oscila entre 11-14 kDa, posee dos secuencias hidrofóbicas internas que median su inserción en RE, dejando la región intermedia hidrofílica, muy conservada, dispuesta a modo de lazo hacia la cara luminal del orgánulo y los extremos N-t y C-t expuestos al citoplasma [Zamyatnin et al, 2006;Hsu et al, 2008;Lee et al, 2010].…”
Section: Bloque Triple De Genesunclassified
“…En cuanto a TGBp3, su secuencia se encuentra escasamente conservada entre homólogos, su estructura es más variable y su tamaño oscila entre 6 y 24 kDa [revisado en Verchot-Lubicz et al, 2010]. De forma general, los virus tipo-potex poseen proteínas TGBp3 de menor tamaño (normalmente 7-8 kDa), con un único dominio TM, hacia N-t, que presuntamente permite la inserción dejando la porción C-t expuesta hacia el citosol y el extremo N-t orientado hacia el lumen del RE [Krishnamurthy et al, 2003;Lee et al, 2010]. Por su parte, las TGBp3 de los virus tipo-hordei suelen ser algo mayores (15-24 kDa) y muchos de los productos de mayor tamaño cuentan con una región N-t rica en residuos de Cys (Fig.…”
Section: Bloque Triple De Genesunclassified